Telomerase activity detected in oral lichen planus by RNA in situ hybridisation: not a marker for malignant transformation. Issue 8 (1st August 2002) - O'Flatharta, C; Leader, M; Kay, E; Flint, S R; Toner, M; Robertson, W; Mabruk, M J E M F
Abstract : Background: Oral lichen planus (OLP) is a chronic inflammatory condition. Clinically, it is characterised by the presence of a white lace-like lesion on the buccal mucosa, tongue, and gingivae, with erosions and ulceration. The World Health Organisation considers OLP to be a premalignant condition. Aims: To investigate expression of the telomerase RNA component (hTR) in OLP compared with normal control buccal mucosa and to assess the possibility of using hTR expression as a marker for malignant transformation in OLP. Methods: hTR expression was analysed in 40 cases of OLP and 18 normal control buccal mucosa samples using an RNA in situ hybridisation approach. Results: Strong hTR RNA expression was seen in the basal, suprabasal, and to a lesser extent in the upper epithelial layers in 36 of the 40 OLP lesions examined. Infiltrating subepithelial lymphocytes in OLP were also shown to express hTR RNA. Weak hTR RNA expression was seen in seven of the 18 normal control buccal mucosa specimens, with expression confined exclusively to the basal layer of the epithelium and absent in the suprabasal and upper layers. Conclusion: The telomerase RNA component hTR is found to be highly expressed in the epithelium of non-dysplastic OLP lesions. It is possible that this high expression is related to the increased cellular proliferation seen in OLP lesions rather than being an indicator of susceptibility to malignancy. Thus, hTR RNA expression may not be a suitable marker for predicting malignant transformation in OLP.